What is not yours is not yours [large type] - Oyeyemi, Helen (Center Point Large Print, 2016)
The stories collected here are linked by more than the exquisitely winding prose of their creator. The reader is invited into a world of lost libraries and locked gardens, of marshlands where the drowned dead live, the Homely Wench Society commits a guerrilla book-swap, and lovers exchange books and roses on St Jordi's Day. It is a collection of towering imagination, marked by baroque beauty and a deep sensuousness.